1992
DOI: 10.1021/ja00050a019
|View full text |Cite
|
Sign up to set email alerts
|

Main chain and side chain chiral methylated somatostatin analogs: syntheses and conformational analyses

Abstract: followed by filtration of the desired salt and vacuum drying.,' Then, 4.5 g (61 "01) of 2-butanol and 2.3 g (20 "01) of the formamidinium salt were stirred under reflux for 21 h. The mixture was cooled to room temperature, washed with 15 mL of Et,O, and concentrated under vacuum. The residue was dissolved in 2 mL of MeOH and chromatographed over silica gel with 1 3 1 CH2Cl2/MeOH eluent. Weobtained 1.29 g (8.4 mmol, 42%) of isouronium salt 8 as a highly hygroscopic, glassy solid (under vacuum), that fused to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 6 publications
(6 reference statements)
7
79
0
Order By: Relevance
“…2). This result is in accord with previously described results (20) -] with an attendant increase in binding to AtT20 cells. Also in agreement with these earlier studies, the (2R,3R)-isomer 6 bound much less tightly to sstr2.…”
Section: Resultssupporting
confidence: 94%
“…2). This result is in accord with previously described results (20) -] with an attendant increase in binding to AtT20 cells. Also in agreement with these earlier studies, the (2R,3R)-isomer 6 bound much less tightly to sstr2.…”
Section: Resultssupporting
confidence: 94%
“…Interestingly, Goodman and coworkers illustrated that in SRIF analogues, which bind selectively to sst 2 2/3/5 , the side chains of DTrp 8 , Lys 9 , Phe 7 and Phe 2 constitute the most essential elements necessary for binding. 15,16 In their pharmacophore model, DTrp 8 and Lys 9 were at a close proximity of ∼5 Å, which is similar to the sst 2 pharmacophore. The aromatic ring at position 7, Phe 7 is farther away from DTrp 8 (7 to 9 Å) and Lys 9 (9 to 11 Å), and is not present in the sst 2 pharmacophore.…”
Section: Comparison Of the Sst 2 -Selective Versus Sst 2/3/5 -Selectimentioning
confidence: 78%
“…On the basis of these 3D structures of the free peptides, a pharmacophore model was proposed for SRIF analogues binding to sst 2/5 (and sst 3 ). [15][16][17][18] In this model, the side chains and the relative spatial arrangement of DPhe 2 , Phe 7 , DTrp 8 and Lys 9 constitute the most essential elements necessary for binding ( Figure 3C). The side chain of DTrp 8 is in close proximity to the side chain of Lys 9 (∼5 Å), whereas the side chain of Phe 7 is about 7 − 9 Å away from the side chain of DTrp 8 and 9 − 11 Å from the side chain of Lys 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The two basic ring conformations found in the crystal would then correspond to the two conformations found by NMR in solution. Huang et al (1992) made detailed predictions for 'flat' and 'folded' conformations of the same cyclic hexapeptide c[Pro6-Phe7-(D)-TrpS-Lys9-Thrl°-Phe ll] which are compared with our results in Table 4. It will be seen that the qo and ~b torsion angles of the -(D)-Trp 8-and -Lys 9-residues for both their structures and our molecules I, II and III are all typical for type II'/3-turns.…”
Section: Molecular Conformationsmentioning
confidence: 99%
“…NMR studies by Kessler et al (1983) also indicated a type II'/3-turn. Huang et al (1992) and He, Huang, Raynor, Reisine & Goodman (1993), using 500MHz two-dimensional NMR, binding studies and conformational analysis of methylated derivatives, showed that although the side chains are conformationally flexible, the biologically active conformation of this cyclic hexapeptide probably involves the trans rotamer of D-Trp 8 and the gauche-(g-) rotamer of Lys 9.…”
Section: Introductionmentioning
confidence: 99%